2018
DOI: 10.1212/cpj.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of Alice in Wonderland syndrome in a cohort with vestibular migraine

Abstract: BackgroundAlice in Wonderland syndrome (AIWS) is a rare sensory perception disorder, most often caused by migraine in adults. We aimed to characterize the clinical characteristics of AIWS in a cohort of vestibular migraine (VM) patients.MethodsRetrospective chart review of patients diagnosed with VM seen between August 2014 and January 2018.ResultsSeventeen patients were identified (10 women) with a median age at onset of 45 years (range 15–61 years), and median age at presentation of 49 years (range 17–63 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
2
25
1
1
Order By: Relevance
“…Fascinatingly, VM episodes were associated with Alice in Wonderland syndrome (AIWS) dysperceptions as well (Table ); 6.9% described extrapersonal misperceptions (out‐of‐body experience, derealization), 6.9% reported visual distortions, and 3.1% experienced somesthetic distortions. These dysperceptions are described in detail elsewhere …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fascinatingly, VM episodes were associated with Alice in Wonderland syndrome (AIWS) dysperceptions as well (Table ); 6.9% described extrapersonal misperceptions (out‐of‐body experience, derealization), 6.9% reported visual distortions, and 3.1% experienced somesthetic distortions. These dysperceptions are described in detail elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…These dysperceptions are described in detail elsewhere. 69 Interictal Symptoms.-During the interictal period, vestibular symptoms were also extremely common ( Table 7). The vast majority described some degree of VID (88.6%), and experienced dizziness with a variety of visual stimuli, most commonly supermarket aisles, busy patterns, movies (3D, IMAX, and action), first-person shooter videogames (where the player sees the action through the eyes of the avatar), scrolling on electronic screens (eg, smart phones, tablets, and computers), optic flow (eg, driving past a row or trees or concrete barriers), and rapidly moving or spinning objects (eg, windshield wipers, and ceiling fans).…”
Section: -Classification and Definition Of Vestibular Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some patients report tinnitus, fullness of the ear, palpitations, and even mild and transient hearing loss, during their episodes [18]. Several authors have described an accompanying Alice in Wonderland Syndrome -a rare and fascinating sensory perception disorder, with the symptoms of visual distortions, extrapersonal misperceptions, or somesthetic distortions [16,45]. Some studies show that VM patients are significantly more anxious and agoraphobic, have depression symptoms and insomnia, have higher sensitivity to separation, and are prone to seek medical reassurance [16,46].…”
Section: Other Symptomsmentioning
confidence: 99%
“…For example, a case of abdominal colic was found to have occurred with AIWS [18]. Another study reported that nearly 77% of AIWS occurred during the vestibular migraine [19]. .…”
Section: Global Publication Trends On Aiwsmentioning
confidence: 99%